2019
DOI: 10.4236/abc.2019.93009
|View full text |Cite
|
Sign up to set email alerts
|

Capture Reagent and Strategy for Retrieving Albumin-Bound Ligands from Plasma

Abstract: A capture strategy is described and demonstrated for retrieving ligand entities in plasma that bind Human Serum Albumin. The method has applications for both exogenous and endogenous ligands. Exogenous ligands include drug candidates, performance enhancing drugs and toxic nerve agents that also interact quite strongly with HSA. Endogenous ligands are natural circulating compounds whose abundance corresponds to normal hemostasis or elevated levels that could be disease-specific molecular biomarkers. Melting cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Faroongsarng [30] studied assessment of the dissociation energies of diazepam and ibuprofen bound on HSA by DSC method and found that the denaturation of HSA incubated with the drugs was done at higher temperatures than HSA itself depending on drugs′ concentrations. Similar findings were demonstrated by other authors [31,32]. The thermograms of free HSA and HSA (fixed concentrations) in the presence of different TB concentrations are shown in Figure S1.…”
Section: Resultssupporting
confidence: 90%
“…Faroongsarng [30] studied assessment of the dissociation energies of diazepam and ibuprofen bound on HSA by DSC method and found that the denaturation of HSA incubated with the drugs was done at higher temperatures than HSA itself depending on drugs′ concentrations. Similar findings were demonstrated by other authors [31,32]. The thermograms of free HSA and HSA (fixed concentrations) in the presence of different TB concentrations are shown in Figure S1.…”
Section: Resultssupporting
confidence: 90%
“…Samples were prepared by adding specific reaction components to pre-prepared media. For DSC melting experiments, the sample heating rate was approximately 1 °C/min while monitoring changes in the excess heat (microwatts) of the sample versus temperature [6][7][8]. In their primary form, melting curves or thermograms are displayed as plots of changes in microwatts measured for the sample, versus temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We found an increase in the melting temperature for a small fraction (~10%) of the HSA pool could explain the observed HDC shift (Supplemental Figure 3). Changes in HSA melting temperature could result from new ligand binding, protein interactors, or tertiary structure (48)(49)(50). Here, we tested for structural changes of HSA through analysis of covalently modified amino acid profiles between the RA and non-RA samples.…”
Section: Structural Changes In High Abundance Proteinsmentioning
confidence: 99%